The development, validation and application of analytical methods for the analysis of drugs of abuse - Maguire, Richard (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2001)
There are five chapters presented in this thesis. The first chapter deals with development and validation of a HPLC method for the analysis of MDMA in illicitly produced Ecstasy tablets. In all 100 tablets were analysed and the MDMA content on average was found to be 79.01 mg. The second chapter involved the analysis of route specific compounds (two pyrimidines and N-formyl BDB) derived from MBDB that had been synthesised via the Leuckart route. HPLC and GC-MS methods were developed and validated for the analysis of the three target compounds. Solid phase extraction and liquid-liquid extraction were assessed as potential methods for the extraction of the three target compounds from MBDB synthesised via the Leuckart route. Street samples of MBDB were analysed and it was discovered that three of the tablets were likely to have been synthesised via Leuckart route.Several routes of synthesis of MDA, MDMA, MDEA, MBDB and 4-MTA were investigated in the Department of Pharmaceutical Chemistry. The third chapter involved subjecting impurities, intermediates and products generated by the routes investigated, to GC-MS analysis. Mass spectral data recorded was incorporated into a software based library which could be used as a forensic tool for the attempted identification of routes of synthesis. Samples of licitly prepared Ecstasy and samples of illicitly prepared Ecstasy were subjected to GC-MS analysis. Where possible, routes of synthesis were identified with the aid of the library.
Keywords: Pharmacology Pharmacy, Ph.D.; Ph.D. Trinity College Dublin